Psilocybin as a new way for depression treatment - Pawlicki, Mateusz Maciej; Kłos, Aleksandra; Stachyrak, Karol; Mika, Dawid; Mazur, Bartosz; Turek, Kamila; Lambach, Maciej; Greguła, Anna; Mazurek, Aleksandra; Wilanowska, Wiktoria (Journal of Education, Health and Sport, 2024)
Introduction: Mental disorders are common and still growing problem around the globe. Significantly decreasing quality of life, they are often source of true suffering for patients and their families leading to further health issues or even dramatic outcomes resulting in death. As public awareness rises, more and more people understand risks and tend to look for help as fast as possible. Currently available treatment methods are not always efficient enough to deal with more complex cases. Therefore it is important to look for new therapy options incrementing chances of fast and successful treatment. Results: Studies showed that psilocybin is not only able to lower depression and anxiety scores in patients with major depressive disorders or with serious life-threatening conditions but also proved this effect to be long-lasting. At the same time, no or little adverse side effects were noticed. Conclusions: Psilocybin is potentially a good method for depression treatment in some groups of patients. It should be considered if other, better known therapies show little or no effects.